2009
DOI: 10.3892/ijo_00000190
|View full text |Cite
|
Sign up to set email alerts
|

Glypican-3 is a useful diagnostic marker for a component of hepatocellular carcinoma in human liver cancer

Abstract: Abstract. Primary liver cancers are classified into three types based on their morphology and cytogenetic characteristics hepatocellular carcinoma (HCC), intrahepatic cholangiocarcinoma (ICC) and combined hepatocellular and cholangiocarcinoma (CHC). It is often difficult to distinguish these liver tumors. Glypican-3 (GPC3) is serological and histochemical marker of hepatocellular carcinoma. In order to separate these three types of liver cancers, we analyzed the GPC3 expression in 85 liver resection specimens,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 44 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…The HCC-selective target, glypican-3 (GPC3), is a known pathological marker of HCC and is overexpressed in approximately 75% of HCC [9][10][11][12]. GC33 (a.k.a.…”
Section: Introductionmentioning
confidence: 99%
“…The HCC-selective target, glypican-3 (GPC3), is a known pathological marker of HCC and is overexpressed in approximately 75% of HCC [9][10][11][12]. GC33 (a.k.a.…”
Section: Introductionmentioning
confidence: 99%
“…High GPC3 expression levels in HCC may suggest poor differentiation, early metastasis, and poor prognosis [29] . A previous report showed that GPC3 immunostaining was positive in 78.3% (36/46) of HCCs and 72.7% (8/11) of the HCC components of CHC sections, yet negative in ICCs [30] . In our study, GPC3 immunostaining was positive in 79.2% (95/120) of HCCs and 82.4% (14/17) of CHCs, but few ICC (6/50), metastatic adenocarcinoma (2/20), and benign liver lesion (2/28) samples.…”
Section: Discussionmentioning
confidence: 82%
“…It has been reported that cell-cycle regulators and cell division factors like BUB1, CDC25B, CDC45, CENPA, PRC1, PRIM1, RRM2, SPC24, and growth factor receptors like ADGRD1 and HMMR are up-regulated by the TSPY gene [ 102 ]. Shirakawa and colleagues showed the co-expression of TSPY and Glypican-3 ( GPC3 ) as a sensitive and specific biomarker of HCC [ 114 ]. Kido and colleagues identified a TSPY co-expression network (TCN) which activated in 30% of males with HCC [ 101 ].…”
Section: Liver Cancermentioning
confidence: 99%